Nirmatrelvir/ritonavir for patients with SARS-CoV-2 infection and impaired kidney function during the Omicron surge - Jiayi Yan; Jiayi Yan; Hong Cai; Jieying Wang; Mingli Zhu; Ping Li; Peiying Li; Bin Wu; Xiajing Che; Leyi Gu; Shan Mou; Shan Mou (Frontiers Media S.A., 2023)
Background: Nirmatrelvir/ritonavir has demonstrated effectiveness in high-risk patients with coronavirus disease 2019 (COVID-19). However, investigations on the efficacy and safety of nirmatrelvir/ritonavir in patients with kidney dysfunction are limited.Methods: Data were collected from the patients admitted to a COVID-19 referral center in Shanghai, China. Patients were at least 18 years of age and had a baseline estimated glomerular filtration rate (eGFR) of <60 ml/min/1·73 m2. The primary endpoint was a composite of all-cause mortality, intensive care unit admission, or cardiovascular events. The secondary endpoint was viral shedding.Results: Among the 195 participants, 73 received nirmatrelvir/ritonavir. A lower risk of the primary endpoint was observed in nirmatrelvir/ritonavir recipients compared with non-recipients [adjusted HR 0.56 (95% CI: 0.32-0.96); p = 0.035]. Nirmatrelvir/ritonavir recipients experienced a shorter duration of viral shedding [adjusted HR 3·70 (95%CI: 2.60-5.28); p < 0.001) and faster viral load clearance versus non-recipients. Among the nirmatrelvir/ritonavir users, earlier initiation of nirmatrelvir/ritonavir within 5 days since COVID-19 diagnosis was related with shorter viral shedding time (adjusted HR 7.84 [95% CI: 3.28-18.76]; p < 0.001) compared to late initiation. No patients reported serious adverse events during treatment.Conclusion: Our findings support the early initiation of nirmatrelvir/ritonavir for high-risk patients with impaired kidney function. This could improve patient outcomes and shorten the viral shedding period.